Numerical Simulation of Hot Forging Process of KIA Car Brake’s Output Shaft - saeid Hashemian; Peyman Mashhadi Keshtiban; Abuzar Es'haghi Oskui (International Journal of Advanced Design and Manufacturing Technology, 2022)
The present study investigates the production process by closed die forging method of one of the sensitive and safe parts of KIA car brake, which is affected by various mechanical and thermal stresses in its operating conditions; therefore, in the present research, the application of this forming method in the Iranian automotive industry has been discussed. In this study, an attempt was made using finite element analysis in ABAQUS software to determine the maximum force required for forging this part. In addition, the influence of various parameters such as the temperature of the part during the forming process, the coefficient of friction between the part and the die, as well as the strain rate have been investigated. The results indicated that the friction coefficient has a significant effect on the maximum required force, and the maximum values of the load increase with increasing the friction coefficient; but the remarkable result is that the effect of this coefficient is negligible from a value onwards. This point is consistent with the observations in practice. Besides, a strong dependence of the results on the loading speed was observed, and the required force has increased with increasing loading speed for reasons such as the strain hardening phenomenon. Also, the force required for forging has decreased with increasing the temperature, which is due to reduced material strength. This reduction from 900°C to 1000°C is less than 2%, while it is approximately 40% from 1000°C to 1100°C, which is consistent with the experimental reports.